Cognitive Predictors and Risk Factors of PTSD Following Stillbirth: A Short‐Term Longitudinal Study. Issue 2 (27th March 2015) - Horsch, Antje; Jacobs, Ingo; McKenzie‐McHarg, Kirstie
Abstract: This short‐term longitudinal study investigated cognitive predictors and risk factors of posttraumatic stress disorder (PTSD) in mothers following stillbirth. After a stillbirth at ≥ 24 weeks gestational age, 65 women completed structured clinical interviews and questionnaires assessing PTSD symptoms, cognitive predictors (appraisals, dysfunctional strategies), and risk factors (perceived social support, trauma history, obstetric history) at 3 and 6 months. PTSD symptoms decreased between 3 and 6 months (Cohen's d ranged .34–.52). Regression analyses also revealed a specific positive relationship between Rumination and concurrent frequency of PTSD symptoms (β = .45). Negative Self‐View and Negative World‐View related positively and Self‐Blame related negatively to concurrent number of PTSD symptoms (β = .48, .44, −.45, respectively). Suppression and Distraction predicted a decrease and Numbing predicted an increase in time‐lagged number of PTSD symptoms (β = −.33, −.28, .30, respectively). Risk factors for PTSD symptoms were younger age (β = −.25), lower income (β = −.29), fewer previous pregnancies (β = −.31), and poorer perceived social support (β = −.26). Interventions addressing negative appraisals, dysfunctional strategies, and social support are recommended for mothers with PTSD following stillbirth. Knowledge of cognitive predictors and risk factors of PTSD may inform the development of a screening instrument.